Agreement of post-LASIK corneal power and corneal thickness measurements by pentacam and GALILEI corneal tomography systems. Issue 1 (January 2019) - Hsieh, Yun-Hsiu; Weng, Tzu-Heng; Chou, Yu-Ching; Wu, Kuan-Liang; Liang, Chang-Min; Tai, Ming-Cheng
Abstract : Background: Post-LASIK corneal conditions cannot be accurately measured by traditional optometric approaches. Therefore, we aimed to analyze the agreement of two rotating Scheimpflug cameras in corneal assessment. Methods: Fifty otherwise healthy volunteers who had undergone LASIK were recruited in this study. The values of mean and central total corneal power (TCP), including TCP1, TCP2, and TCP-IOL, were measured by GALILEI Scheimpflug camera. The values of total corneal refractive power (TCRP) readings at both 2 mm ring and 3 and 4 mm zones were detected by Pentacam Scheimpflug camera. Central corneal thickness (CCT) and thinnest corneal thickness (TCT) were quantified by GALILEI and Pentacam respectively. Paired t -tests and Bland–Altman analyses were used to evaluate statistical differences between measurement results obtained by GALILEI and by Pentacam. Results: Among these 50 subjects, the mean and central TCP1 values (37.31 ± 2.61 and 37.27 ± 2.64) derived from GALILEI measurements were consistent with the TCRP values (37.08 ± 2.76, 37.11 ± 2.74, and 37.19 ± 2.68; p > 0.05) determined by Pentacam at the 2 mm ring apex, 3 mm zone apex, and 4 mm zone apex. There were no statistically significant differences in central corneal thickness (CCT) values measured by the two cameras (463.64 ± 55.67 μm for GALILEI and 470.69 ± 44.04 μm for Pentacam, respectively; p > 0.05). However, the limits of agreement were wide when comparing mean TCP1 (−1.4 to 1.8 D, −1.4 to 1.8 D, and −1.3 to 1.6 D), central TCP1 (−1.2 to 1.6 D, −1.2 to 1.6 D, and −1.2 to 1.4 D) and CCT (−77.2–63.0 μm). Conclusion: Corneal power and corneal thickness are disparate post-LASIK evaluation parameters when comparing the utility of GALILEI with that of Pentacam.